2013
DOI: 10.4103/0973-029x.125208
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiology of merkel cell

Abstract: The objective of this review is to introduce Merkel cells (MCs), to provide a basic overview on the theoretical background of function, development and clinical importance of MCs. The origin of human MCs have been controversial. Some investigators believe that it is a neural crest derivate, whereas others have proposed that it is a differentiation product of the fetal epidermal keratinocytes. MCs are cells primarily localized in the epidermal basal layer of vertebrates and concentrated in touch-sensitive areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…As such, the system can be readily adapted to meet the needs of different researchers. We anticipate that modifications of this protocol will be useful for the study of other cell types that are difficult to transfect, including mechanosensory cells in other tissues such as Merkel cells in the skin 19 .…”
Section: Introductionmentioning
confidence: 99%
“…As such, the system can be readily adapted to meet the needs of different researchers. We anticipate that modifications of this protocol will be useful for the study of other cell types that are difficult to transfect, including mechanosensory cells in other tissues such as Merkel cells in the skin 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Merkel cell carcinoma (MCC) is a rare neuroendocrinal tumor, basically originated in skin [1,2]. In 1887, Friedrich Sigmund Merkel was the one who discovered merkel cells (MC) at the tip of rete ridges of epidermis [3].…”
Section: Introductionmentioning
confidence: 99%
“…However, origin of MC is thought to be different in both the epithelium. Two school of thoughts are present; one is ''neural crest origin'' and another one is ''Epidermal origin'' [2]. As the oral mucosa develops from ectoderm, it was thought that Merkel cells in oral mucosa originates from neural crest cells [6].…”
mentioning
confidence: 99%
“…A pathologic study performed by Skelton et al at the Armed Forces Institute of Pathology [15], examined 132 cases of MCC to determine whether there were clinical or histological characteristics that predict its behaviour. They found that cell size, mitosis, and tumour size were all predictive of survival.…”
Section: Prognostic Factorsmentioning
confidence: 99%